Developing communities - Kenny, Susan; Hand, Tammy (South Melbourne, Victoria Cengage Learning Australia, 2022)
Community development is a living field of theory and practice. The enduring features of community development include the commitment to human rights; the empowerment of ordinary people, and especially those who are disadvantaged and oppressed: and support for communities to exert greater control over decisions that affect their lives.
1. The nature of community development -- 2. Local and global contexts -- 3. Theoretical perspectives and concepts -- 4. Community development and the state -- 5. Processes and practices -- 6. Community organisations -- 7. Activities and practices -- 8. Working for solidarity - collection action across difference -- 9. Funding, research, and evaluation -- 10. difficulties and dilemmas -- 11. Challenges and opportunities for the future.
Includes bibliographical references and index.
Keywords: Community development -- Australia -- Study and teaching; Social classes -- Australia